Characteristics and controlling factors of deep buried-hill reservoirs in the BZ19-6 structural belt, Bohai sea area - Mingcai Hou; Haiyang Cao; Huiyong Li; Anqing Chen; Ajuan Wei; Yang Chen; Yuechuan Wang; Xuewei Zhou; Tao Ye (Natural Gas Industry B, 2019)
The BZ19-6 deep buried-hill structural belt in the southwest of Bozhong Sag, Bohai Bay Basin, is a newly discovered super-giant oil and gas bearing area. The study on its reservoirs is still in the early stage, and the characteristics and control factors of reservoir development are not understood deeply. In this paper, cores, sidewall cores, rock sections were analyzed and described. Then, based on regional structural setting, mud logging and logging data, the buried-hill reservoirs in this area were analyzed from the aspects of petrological characteristics, reservoir space types and physical properties, the inherent factors influencing the development of the reservoirs were discussed, and distribution laws of the reservoirs were investigated. And the following research results were obtained. First, the deep buried-hill reservoirs of this belt are a pan-buried hill reservoir system composed of the Palaeocene–Eocene Kongdian Fm glutenite in the upper part and the Archean buried-hill metamorphic granite in the lower part. A multi-layer reservoir structure of glutenite pore zone, weathering crust dissolution fracture zone and inner fracture zone is formed. These reservoirs are complex in genesis and diverse in type. Second, the Archean buried-hill metamorphic granite reservoir can be vertically divided into weathering crust, inner fracture zone and tight zone, and it presents the dual characteristics of porous and fractured media. Third, the buried-hill weathering crust is mainly affected by strong dissolution and leaching superimposed with fracturing, forming fractured-porous reservoir space. The reservoir of inner fracture zone is mainly controlled by the superimposition of three-phrase fractures, which forms the main development period of buried-hill fractures since the Yanshanian. Fourth, the glutenite of Kongdian Fm is a typical sieve deposit and it is mainly controlled by the late dissolution. Fifth, migmatization and supercritical fluid cryptoexplosion play a constructive role in the development of the reservoirs. In conclusion, the understanding of buried-hill glutenite and metamorphic reservoir system developed in this belt is conductive to determining the target and direction of next oil and gas exploration in this area. Keywords: Bohai bay basin, Bohai sea area, BZ19-6 deep buried-hill structural belt, Archean, Deep metamorphic granite reservoir, Paleogene, Glutenite reservoir, Dissolution, Structural fracture